Utility of [18F] Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Scan in Inflammatory Myopathies: Case Report and Literature Review - Juan Pablo Rivas-de Noriega; Javier Andrés Galnares-Olalde; Javier Zúñiga-Varga; Juan Pablo Herrera-Félix; Marco Antonio Alegría-Loyola; Alonso Turrent-Carriles (Case Reports in Rheumatology)
Introduction. Inflammatory myopathies are a rare group of diseases characterized by proximal weakness. Incidence ranges from 7.98/million/year and prevalence at 14/100,000. The utility of [18F] fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) scan is increasing for the complementary diagnosis of myopathies. Case Report. An 84-year-old male was admitted with a history of difficulty rising from a chair and a fall. Laboratory results showed increased creatine kinase levels of more than 50 times the normal reference values. Electromyography (EMG) showed myopathic changes, and FDG-PET/CT scan showed increased FDG uptake in bilateral quadriceps. A biopsy was performed revealing lymphocytic predominant infiltrates and myonecrosis. Prednisone and intravenous immunoglobulin (IVIG) were administered with strength improvement. The patient was discharged for further follow-up. Discussion. FDG-PET/CT in inflammatory diseases has proven useful as muscle fibers have increased FDG uptake. In some cases, FDG-PET/CT is also useful in determining associated neoplastic diseases.